Retinal Vascular Changes during the Menstrual Cycle Detected with Optical Coherence Tomography Angiography - Linning Guo; Chenlei Zhu; Ziqi Wang; Zhiqiang Gao; Zongduan Zhang; Qintuo Pan (Journal of Ophthalmology)
Purpose. To evaluate the effects of the menstrual cycle on the retinal vascular status of healthy women by optical coherence tomography angiography (OCTA). Materials and Methods. Healthy women with regular natural menstrual cycles of 28 to 30 days were recruited for this prospective study. The women’s retinal vascular status was measured by OCTA at 3 time points: the early follicular, ovulatory, and midluteal phases of the menstrual cycle. The main outcome measures were foveal avascular zone (FAZ) parameters, perfusion density (PD) percentage in the superficial retinal capillary plexus (SCP), and PD percentage in the deep retinal capillary plexus (DCP). The mean arterial pressure (MAP), spherical equivalent (SE), best-corrected visual acuity (BCVA), intraocular pressure (IOP), and axial (AL) were also measured in a same menstrual cycle. Results. In total, 62 right eyes of 62 women were included in the study. The mean age was 27.0 ± 1.73 (range, 24 to 31) years, and the mean menstrual cycle was 28.90 ± 0.84 (range, 28 to 30) days. The mean values of the DCP-PD parameters were significantly decreased in the nasal and inferior ETDRS subfields during the ovulatory phase. The mean DCP-PD in the nasal ETDRS subfield in the early follicular, ovulatory, and luteal phases was 54.11 ± 2.85, 56.39 ± 3.03, and 55.70 ± 3.27, respectively. The mean DCP-PD in the inferior ETDRS subfield in the early follicular, ovulatory, and midluteal phases was 52.90 ± 3.30, 54.86 ± 2.51, and 55.21 ± 2.64, respectively. No significant differences were found in MAP, SE, AL, IOP, FAZ area, or other quadrants of PD parameters, and no significant correlation was found between parameters by OCTA and age, MAP,SE, axial length, or IOP. Conclusions. The DCP-PD decreased in the nasal and inferior ETDRS subfields during the ovulatory phase in our study. This may indicate the need to consider the menstrual phase when interpreting DCP-PD parameters by OCTA in healthy women.